EFEKTIFITAS PENERAPAN QANUN NOMOR 14 TAHUN 2003 TENTANG KHALWAT DI KABUPATEN ACEH BESAR - Faisal Faisal (Universitas Islam Negeri Ar-Raniry, 2013)
The Government of Aceh form Qanun No. 14 of 2003 on Klalwat (seclusion) by Regulation No. 5 of 2000 on the implementation of Shari'ah. In the regulation stated that the Islamic Sharia Qanun No. 14 of 2003 on Seclusion / Impropriety, defined as